An empirical study of the socio-demographic profile as a determinant of the level of motivation and training among the employees of the Ministry of Internal Affairs - Todorova Irena (2024)
The article presents the eternal relevance between the socio-demografic profile as a determinant of the level of motivation and training among the employees of the Ministry of Internal Affairs (MIA). The main goal of the author is to determine that the measured socio-demographic profile allows the Ministry of the Internal affairs to adapt and continuously improve the models for management impact according to the changing socio-economic reality. The variety of activities carried out by the state administration determine its complex organizational structure, which implies the involvement of employees of different working ages and with different professional competence.